Evaluating the dissemination of Body & Soul, an evidence-based fruit and vegetable intake intervention: challenges for dissemination and implementation research - Allicock, Marlyn (2012)
OBJECTIVE: To evaluate whether the evidence-based Body & Soul program, when disseminated and implemented without researcher or agency involvement and support, would achieve similar results to earlier efficacy and effectiveness trials. DESIGN: Prospective group randomized trial. SETTING: Churches with predominantly African American membership. PARTICIPANTS: A total of 1033 members from the fifteen churches completed baseline surveys. Of these, 562 (54.4%) completed the follow-up survey six months later. INTERVENTION: Church-based nutrition program for African Americans that included pastoral involvement, educational activities, church environmental changes, and peer counseling. MAIN OUTCOME MEASURE: Daily fruit and vegetable (FV) intake was assessed at pre- and post-test. ANALYSIS: Mixed-effects linear models. RESULTS: At posttest, there was no statistically significant difference in daily servings of FV between the early intervention group participants compared to control group participants (4.7 vs, 4.4, P=0.38). Process evaluation suggested that added resources such as technical assistance could improve program implementation. CONCLUSIONS AND IMPLICATIONS: The disseminated program may not produce improvements in FV intake equal to those in the earlier efficacy and effectiveness trials, primarily due to lack of program implementation. Program dissemination may not achieve public health impact unless support systems are strengthened for adequate implementation at the church level.